(untitled) (Ibrahim Cardiac Medical Journal, 2011)
This cross-sectional study was conducted on doctors, nurses and support staffs serving at the Emergency Department of Ibrahim Cardiac Hospital and Research Institute (ICHRI) to seek their opinion about the status of management services available at the Emergency Department (ED) of the Institute. Of the total respondents 20 were on duty physicians, 21 were on duty nurses and 18 were support staffs. Apart from the respondents, 34 check-lists were used by 3 (three) independent observers to monitor the daily ongoing activities of the Emergency Department during the period of data collection. This study analyzed the service providers’ perspective about management of Emergency Department. As doctors’ opinion was sought, 45% of them expressed their satisfaction at the services delivered at ED and 40% were more or less satisfied. Very few were either highly satisfied (5%) or grossly dissatisfied (10%). As regard to work-load, thirty percent opined that ED was overloaded. However, majority believed that ED was adequately equipped (75%) to deal with cardiac emergencies which bear consistency with the views expressed by patients/clients. Forty percent held the view that support staffs were not adequate to run the Emergency Department smoothly. The views expressed by the nurses shows that majority (62%) of them was satisfied working at ED and informed that they did not feel any problem in carrying out their assigned duties. They also were of the opinion that ED was adequately equipped but there was inadequacy of support staff (57.1%) keeping consistency with doctors’ opinion. They, however, mentioned some other problems like inadequacy of nurses, porter and cleaners in every shift, security problem, lack of dress locker, dress changing room and dining space. Over 22% of the support staffs viewed ED as overloaded which correlates well with doctors’ opinion. All other opinions were almost the same as those of doctors and nurses. One important issue they raised was the lack of rest room for them (22.2%). The findings of cardiac emergency services obtained through check-list were fairly comparable with the opinions expressed by the patients and service providers. However, the views expressed by the patients and service providers about wardboys/ayas did correlate with the data obtained through check-list and were inappreciably low (29.4%). According to service providers the Emergency Department is well-studded to manage all the cardiac emergencies. However, specific problems identified by different stakeholders need to be critically appraised by the authority to improve the services further. Ibrahim Card Med J 2011; 1(1):22-26